Bioinspired Stochastic Design: Tough and Stiff Ceramic Systems. (16th November 2021) - Yazdani Sarvestani, Hamidreza; Aranguren van Egmond, Derek; Esmail, Ilhan; Genest, Marc; Paquet, Chantal; Ashrafi, Behnam
Abstract: Ceramics possess desirable stiffness, compressive strength, and thermal properties compared to alternative material classes. Despite this, the adoption of ceramics into advanced industries has been hindered by their inherent brittleness. Using a state‐of‐the‐art manufacturing platform, the authors incorporate disordered microstructural features inspired by those found in natural, impact‐resistant organisms using tessellated ceramic cells. To precisely mimic these natural patterns, a disorder parameter is introduced to modulate the stochasticity of the ceramic architectures. By modifying simple geometrical features such as cut depth and the disorder parameter, the energy absorption is dramatically improved, and the stiffness of the system can be tailored. It is found that the stochastic designs exhibit elevated damage tolerance, denoted by higher dynamic energy absorption (up to 330% for the 3rd impact) and stiffness (up to 200% for the 3rd impact) than both monolithic and perfectly hexagonal architectures. The results show a superior multi‐hit resistance owing to optimal cut depth and stochasticity which give access to extrinsic toughening mechanisms that can be influenced through design parameters. This highly‐scalable, digital manufacturing platform for creating numerically programmable architectures propels the automated production of intelligent, high‐performance, and tailorable ceramic systems for industrial applications in aerospace, protective devices, and medicine. Abstract : Recently researchers have begun to identify the full range of benefits associated with natural disordered materials. A new class of high‐performance ceramics is defined featuring bio‐inspired stochasticity in their architectures. These materials are manufactured using scalable techniques enabling the precise control over the degree of stochasticity and ceramic cut depth, two parameters that are key to achieving a damage‐tolerant material.